Sodium valproate induced gingival enlargement with pre-existing chronic periodontitis - Vaibhavi Joshipura (Wolters Kluwer Medknow Publications, 2012)
Gingival enlargement is a common clinical feature of gingival and periodontal diseases. Currently, more than 20 prescription medications are associated with gingival enlargement. Although the mechanisms of action may be different, the clinical and microscopic appearance of drug-induced gingival enlargement is similar with any drug. Gingival enlargement produces esthetic changes, and clinical symptoms including pain, tenderness, bleeding, speech disturbances, abnormal tooth movement, dental occlusion problems, enhancement of caries development and periodontal disorders. Sodium valproate is considered to produce gingival enlargement, but very rarely. This case report features sodium valproate induced gingival enlargement in a patient with pre-existing chronic periodontitis, who came to the Dental Department, Chinmaya Mission Hospital, Bangalore. The case is special as the patient did not develop the enlargement in spite of taking phenytoin for 1 year and developed enlargement with sodium valproate within 6 months.